Tackling Intruders in Wireless Mesh Networks - Pathan, Al-Sakib Khan; Khanam, Shapla; Saleem, Habibullah Yusuf; Abduallah, Wafaa Mustafa (CRC Press, USA, 2013)
This chapter presents a different approach of tackling intruders in Wireless Mesh Networks (WMN). Traditional approach of intruder detection and prevention suggests purging out intruders immediately after their detection. In our work, we take a different approach to tackle intruder rather than purging it out of the network unless it is marked as a direct threat to the network’s operation. Our intrusion tackling model is termed ‘Pay-and-Stay’ (PaS) model which allows a rogue node to stay in the network only with the expense of doing some traffic forwarding tasks in the network. Failing to carry out the required tasks of packet forwarding disqualifies the node permanently and eventually that rogue entity is purged out. Alongside presenting our approach, we briefly talk about other available literature, essential knowledge on wireless network intrusion detection and prevention, and status of intrusion related works for WMN.